Frankenstein: Dead and Alive - Book 3 Book three, Dead and alive - Koontz, Dean R. 1945- (Dean Ray) (New York : Bantam Books, 2009)
Frankenstein's creation, now calling itself Deucalion, faces the final confrontation with its creator, but first they must face an indestructible nightmare entity, as all of the mad scientist's creations return to destroy him.
Keywords: Frankenstein (Fictitious character) -- Fiction; Scientists -- Fiction; Monsters -- Fiction; New Orleans (La.) -- Fiction; Fiction